Analisis akuntabilitas pengelolaan dana desa dalam meningkatkan pemberdayaan masyarakat di Desa Darunu Kecamatan Wori Kabupaten Minahasa Utara: Studi kasus pelaksanaan pembangunan wisata Mangrove - Kantale, Vira A.; Poputra, Agus T.; Wokas, Heince R. N. (Riset Akuntansi dan Portofolio Investasi, 2025)
This study aims to analyze the accountability of village fund management in supporting community empowerment, with a specific focus on the development of mangrove tourism in Darunu Village, Wori District, North Minahasa Regency. Using a descriptive qualitative approach, data were collected through interviews, documentation, and direct observation of financial management processes from planning to reporting stages. The findings indicate that the village government has implemented accountability principles, including transparency, integrity, responsibility, fairness, balance, clarity, and consistency in managing village funds. These principles ensure that the use of funds can be accounted for both to the community and to relevant authorities, ultimately supporting sustainable tourism development and increasing local economic benefits for the surrounding community. This research contributes to the literature on public sector accounting and good governance at the village level by highlighting best practices in financial accountability and community participation.